Quality of Bali Cattle Oocytes Post Vitrification with the Addition of Antioxidant Glutathione Sulfihydryl (GSH) in Maturation Media - Hidayat, Taufik; firmiaty, sri; syarifuddin, syarifuddin; Sonjaya, h (Fakultas Peternakan, Universitas Padjadjaran, 2024)
The success of oocyte maturation in vitro depends on several factors, namely the type of supplement used in the in vitro maturation medium, the quality of the oocytes used, and the risk of contamination and culture conditions. In vitro culture can cause oxidative stress, generating free radicals that can damage cells, so antioxidants are often added to overcome this problem. This study aimed to determine the effect of adding GSH to the maturation medium on the oocyte quality of Bali cattle after vitrification. This research was conducted at the Emryo In vitro Production Laboratory, Institute for Research and Community Service (LPPM) Building, Hasanuddin University, 2023. The study consisted of 4 GSH treatments: 0 mM, 0.5 mM, 1 mM, and 1.5 mM, with 6 replications. The research variables were viability, fractures of the zona pellucida, cytoplasmic shrinkage, and cytoplasmic lysis in post-vitrification and thawing oocytes. The results showed that adding GSH significantly affected oocyte viability (P<0.05). Oocyte viability in control (without GSH) was significantly lower (P<0.05) compared to the 0.5 mM, 1 mM and 1.5 mm treatments, but between the 0.5 mM, 1 mM and 1.5 mm treatments were not significantly different. The effect of treatment on the fractures of the zona pellucida variables, cytoplasmic shrinkage, and cytoplasmic lysis had no significant effect (P>0.05). It can be concluded that there was an increase in oocyte viability in line with the increase in GSH dose.